Antioxidant and Phytochemical Classification of Medicinal Plants Used in the Treatment of Cancer Disease - HUMPHREY SAMUEL; David Undie; Gideon Okibe; Omeche Ochepo; Fatima Mahmud; Manasseh Ilumunter (Journal of Chemistry Letters)
Cancer remains a major public health concern. While conventional therapies are available, there is a growing interest in exploring natural alternatives with potentially fewer side effects. Medicinal plants rich in antioxidants and specific phytochemicals have emerged as promising candidates in this pursuit. This article reviews the antioxidant and phytochemical profiles of medicinal plants used for cancer treatment. It classifies plants based on the predominant antioxidant and phytochemical groups they possess. Examples of plants containing well-studied antioxidants like flavonoids, phenolics, and terpenoids will be provided, highlighting their potential mechanisms in combating cancer. Additionally, the article categorizes plants based on their prominent phytochemical classes, such as alkaloids, glycosides, and saponins, and discusses their reported anti-cancer properties.